Faktor-Faktor Yang Memengaruhi Intensi Muzakki Dalam Membayar Zakat Di Lembaga - Utari Evy Cahyani; Itsla Yunisva Aviva; Aisa Manilet (Institut Agama Islam Negeri Padangsidimpuan, 2019)
This study empirically explores the determined factors of muzakki intention to pay zakat at the zakat institution (BAZ and LAZ). The determined factors of muzakki intention to pay zakat at the zakat institution in the study comprises attitude, subjective norm, and perceive behavioral control. 100 questionnaires were disseminated to the respondents. The data were analysed using a logistic regression. The result of the study showed that perceive behavioral control positively affected the muzakki intention to pay zakat at the zakat institution. This study implies that necessary the role of muslim scholars, government and zakat institution to attrack muzakki to pay zakat in zakat institution.